Analysis Of Risk Factors For TB Transmission In Healthcare Workers And Optimization Strategies For TB Transmission Prevention At Bun Hospital - Yuly Periostiowati Yuly Periostiowati; Khairulyati Khairulyati (CV. AFDIFAL MAJU BERKAH, 2026)
Prevention and control of Tuberculosis (TB) in healthcare facilities is crucial due to the high risk of transmission among healthcare workers. At BUN Hospital, six nurses were confirmed with TB during the 2025 annual screening, despite the implementation of the four pillars of TB IPC. This community service activity aims to analyze risk factors for TB transmission among healthcare workers and to formulate strategies for optimizing TB transmission prevention. The method used was a stepwise analysis: a fishbone diagram to map root causes, USG analysis to determine problem priorities, and SWOT analysis to formulate strategies. The analysis results were presented through interactive dissemination to management, the IPC Team, Quality Team, doctors, and nurses. The study identified inadequate socialization of TB SOPs and a weak monitoring system as the main risk factors causing suboptimal compliance with PPE use. Two priority strategies were agreed upon: a) periodic socialization and retraining on TB IPC SOPs; b) strengthening the monitoring system for SOP implementation. This activity results in management commitment to follow up on these strategies. It was concluded that optimizing SOP socialization and strengthening the monitoring system for SOP implementation, supported by management commitment, can serve as a strategy for preventing TB transmission among healthcare workers at BUN Hospital.